2012
DOI: 10.1007/s00392-012-0427-3
|View full text |Cite
|
Sign up to set email alerts
|

Severe autonomic failure in moderate to severe aortic stenosis: prevalence and association with hemodynamics and biomarkers

Abstract: In patients with moderate to severe AS prevalence of SAF is high. SAF correlates with hemodynamic and biochemical markers indicating increased risk. Future studies should evaluate the prognostic value of SAF in patients with AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
1
11
0
2
Order By: Relevance
“…In the periphery, 5‐HT is mainly stored in platelet and released after platelet activation. These data suggest that the increase in plasma 5‐HT in severe AS could result, at least in part, from platelet activation induced by shear stress through aortic stenosis and release of dense granule content where 5‐HT is stored . It is interesting to note that the increase in arterial plasma 5‐HT was already detectable in arterial plasma from poststenotic aortic blood indicating that platelet activation and 5‐HT release occur at the aortic valve ostium.…”
Section: Discussionmentioning
confidence: 87%
“…In the periphery, 5‐HT is mainly stored in platelet and released after platelet activation. These data suggest that the increase in plasma 5‐HT in severe AS could result, at least in part, from platelet activation induced by shear stress through aortic stenosis and release of dense granule content where 5‐HT is stored . It is interesting to note that the increase in arterial plasma 5‐HT was already detectable in arterial plasma from poststenotic aortic blood indicating that platelet activation and 5‐HT release occur at the aortic valve ostium.…”
Section: Discussionmentioning
confidence: 87%
“…8 Our study showed comparable results for the parameters of TO and TS for the 2 different groups with MCI and TAC. This, and the fact that HRT alterations have previously been found in a variety of cardiac diseases, [24][25][26][27] points out that not the disease itself, but its impact on cardiac strain, results in the variations of baroreceptor function.…”
Section: Discussionmentioning
confidence: 75%
“…Structural heart diseases lead to reductions in baroreceptor sensitivity . This phenomenon has been demonstrated using HRT parameters in various human cardiac diseases, including coronary artery disease, myocardial infarction, heart failure, and aortic stenosis . The reduction of baroreceptor function after myocardial infarction has been reproduced in several animal studies .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Among different mechanism affected or modified by aortic-valve disease, the autonomic regulation, as assessed by heart rate variability (HRV), has been mainly examined in patients manifesting severe aortic-valve stenosis [7][8][9][10][11]. HRV refers to the interval fluctuations between consecutive heart beats [12,13].…”
Section: Introductionmentioning
confidence: 99%